2004
DOI: 10.3748/wjg.v10.i2.209
|View full text |Cite
|
Sign up to set email alerts
|

Genetic detection of Chinese hereditary nonpolyposis colorectal cancer

Abstract: AIM:To explore the germline mutations of the two main DNA mismatch repair genes (hMSH2 and hMLH1) between patients with hereditary non-polyposis colorectal cancer (HNPCC) and suspected (atypical) HNPCC. METHODS:Genomic DNA was extracted from the peripheral blood of the index patient of each family, and germline mutations of hMSH2 and hMLH1 genes were detected by PCR-single strand conformation polymorphism (PCR-SSCP) and DNA sequencing techniques. RESULTS:For PCR-SSCP analysis, 67% (4/6) abnormal exons mobility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In some populations, such as Portuguese and Brazilian, most of the novel mutations were missense [22,23]. However, most of the novel mutations that were reported by Cui et al [30] were frameshift. In another study, Rey et al reported 6 novel mutations in MMR genes, 2 of which were in hMLH1.…”
Section: Discussionmentioning
confidence: 95%
“…In some populations, such as Portuguese and Brazilian, most of the novel mutations were missense [22,23]. However, most of the novel mutations that were reported by Cui et al [30] were frameshift. In another study, Rey et al reported 6 novel mutations in MMR genes, 2 of which were in hMLH1.…”
Section: Discussionmentioning
confidence: 95%
“…All hMSH2 gene-coding regions and the exon/intron boundaries were PCR amplified and then bidirectionally sequenced. The primers used were designed previously (14) and were available upon request. Large genomic alterations in hMSH2 were screened by a modified multiplex PCR assay described previously (23).…”
Section: Somatic Mutation Screening and Loh Analysismentioning
confidence: 99%
“…From 1995 to 2004, we examined 61 suspected HNPCC families and identified pathogenic germline mutations in the coding regions of hMLH1 , hMSH2 , or hMSH6 (14, Yan H, Jin H, Xue G, Mei Q, Ding F, Hao L, Sun S‐H, unpublished data). To clarify whether the germline mutations in the promoter regions are implicated in the tumorigenesis of HNPCC, we subsequently screened the promoter regions of hMSH2 , hMLH1 , and hMSH6 in 37 suspected HNPCC families.…”
mentioning
confidence: 99%
“…There are very little data on the incidence and spectrum of the MMR gene mutation in HNPCC families from the northern Chinese population. Reports of germline MMR gene mutation in mainland China typically involved only a few families, and one or two larger series were derived from Shanghai, which was also composed of a southern Chinese population 12–15 . With the introduction of national birth control (the one child policy), the study of hereditary disease will become more and more difficult and there is a pressing need to systematically characterize the spectrum of the MMR gene mutation in HNPCC families in different ethnic groups of China, so as to facilitate the future design of a strategy for genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%